A Spatially Distributed Microneedle System for Bioorthogonal T Cell‐Guided Cancer Therapy - Lanya Li; Fei Wang; Shushan Mo; Junyao Deng; Xueyi Wang; Jiacong Ai; Yingxian Xiao; Yan Zeng; Qishan Li; Yixin Zhang; Limin Cai; Zhenhua Li (Advanced Science)
Abstract Chimeric antigen receptor (CAR)‐T cell therapy represents a promising strategy for cancer treatment. However, the diversity of solid tumor antigens and the poor infiltration of CAR‐T cells significantly hinder the efficacy of CAR‐T therapies against tumors. Here, a spatially distributed microneedle system (SDMNS) is developed that leverages bioorthogonal reactions to activate and guide endogenous T cells to tumors for effective destruction. The SDMNS consists of two dissolving microneedles, each loaded with complementary bioorthogonal groups and applied separately to lymph nodes and tumor sites. One microneedle loaded with two dibenzocyclooctyne (DBCO)‐modified antibodies activates T cells and labels them with bioorthogonal groups in lymph nodes. The other microneedle, containing N‐azidoacetylmannosamine‐tetraacylated (Ac4ManNAz) for glycometabolic labeling of tumor cells, and the T cell chemotactic factor IP10, is applied directly to the tumor site. The in vivo studies demonstrate that SDMNS effectively directs the migration and infiltration of endogenous activated T cells into the tumors. Through a bioorthogonal click reaction, DBCO‐modified T cells conjugate with azide (N3)‐modified tumor cells, eliciting robust antitumor immune responses and durable immune memory. The SDMNS offers a novel strategy to overcomes tumor heterogeneity by facilitating the directed migration of endogenous T cells.